Haemodynamic effects of atenolol in patients with coronary artery disease. Issue 1 (January 1978) - Robinson, C; Jackson, G; Fisk, C; Jewitt, D
Abstract : The haemodynamic effects of atenolol, a new cardioselective beta-blocking agent, have been studied at rest in 8 patients with coronary artery disease. The drug was administered intravenously in cumulative doses of 0.03, 0.06, and 0.12 mg/kg body weight. A significant decrease in heart rate was associated with a fall in cardiac output. However, this cardiac output fall was not entiely rate dependent, since stroke volume fell significantly both during spontaneous sinus rhythm and when heart rate was maintained constant by atrial pacing. A dose related and significant reduction occurred in left ventricular dP/dt max without significant change in left ventricular filling pressure or mean aortic pressure. Total peripheral resistance at rest rose after atenolol. The haemodynamic findings more closely resemble those which follow intravenous propranolol than those after intravenous practolol in a similar group of patients. These actions of atenolol suggest that it may be a useful agent in the treatment of patients with angina pectoris.